Biocompatible cationic solid lipid nanoparticles as adjuvants effectively improve humoral and T cell immune response of foot and mouth disease vaccines. Issue 11 (4th March 2020) - Li, Shuai; Yang, Yanli; Lin, Xuan; Li, Zhengjun; Ma, Guanghui; Su, Zhiguo; Zhang, Songping
Highlight: A novel cSLN vaccine adjuvant was synthesized and characterized. cSLN did not destruct assembly structure of iFMDV and increased its T m for 1.2 °C. cSLN facilitated the iFMDV uptake and activation of BMDCs. cSLN stimulated comparable humoral immunity to ISA206. Cellular immune responses in mice was significantly improved by cSLN. Abstract: In this work, we explored the potential of cationic solid lipid nanoparticles (cSLN) as efficient adjuvants for inactivated foot and mouth disease virus (iFMDV) vaccine. The cSLN were prepared by O/W emulsion method with Compritol 888 ATO as lipid matrix, and were modified by cationic lipid Didodecyldimethylammonium bromide (DDAB). The content of cationic lipid was optimized to produce cSLN with appropriate particle size, surface morphology, zeta potential, and polydispersity. Loading iFMDV onto cSLN by electrostatic attraction did not destruct iFMDV particle structure as measured by high performance size exclusion chromatography (HPSEC). Differential scanning fluorimetry (DSF) showed the transition temperature, T m, related to iFMDV dissociation increased for 1.2 °C after loading on cSLN, indicating an enhanced stability of this unstable antigen. The cSLN loaded iFMDV enhanced in vitro antigen uptake and activation of bone-marrow-derived dendritic cells (BMDCs) with augmented expression of CD86, CD40, and MHC I. In animal trials, BALB/c mice were immunized with free iFMDV, antigen adjuvanted with the cSLN, and antigen adjuvanted with Montanide ISA 206 emulsion. Specific antibody titers showed cSLN could stimulate similar FMDV-specific IgG and IgG subclasses antibody level compared with the widely used ISA 206. In addition, cSLN significantly enhanced memory immune response including effector-memory T cells and central-memory T cells compared to free iFMDV antigen and antigen adjuvanted with ISA 206. Taken together the enhanced humoral and T cell immune responses and the antigen structure friendly properties, cSLN can be a potential adjuvant for iFMDV vaccines.